A COMPARATIVE STUDY OF NON-PERFORMING ASSETS OF SELECTED PUBLIC AND PRIVATE SECTOR BANKS IN INDIA (CAHIERS MAGELLANES-NS, 2024)
A sound and healthy banking system is very important for an economy. Non-performing asset (NPA) is the best indicator to judge the health of the banking industry. Banking sector NPAs have become a major concern for the Indian economy.  In this paper both gross NPA and Net NPA are considered. This paper is an attempt to correlate the NPA and ROA of Indian commercial Banks. The sample size is small. Two public sector banks and two private sector banks chosen for the study. Period for this study is 05 years (2020 to2024). It is found that in the period of 05 years gross NPA% is higher in public sector bank i.e., PNB of 10.916% and lower in private sector bank i.e., HDFC Bank with 1.222% mean value. NPA of private sector banks are well under control. Correlation between Net NPA and Net Profit of all the banks show negative correlation. Negative correlation indicates that when NPA will rise then Net profit will be decreased. There is a negative correlation shown in all the selected public and private sector banks in between Net NPA % and Return on Assets (ROA)%. It means increase in NPA leads to decrease in ROA of the banks.